Greenhouse Gas Emissions Dynamics in Restored Fens After In-Situ Oil Sands Well Pad Disturbances of Canadian Boreal Peatlands - Lemmer, Meike; Rochefort, Line; Strack, Maria (Frontiers in Earth Science, 2020)
In-situ oil sands well pads impact the vast mosaic of boreal wetlands and uplands. Peatland restoration in these regions aims at reestablishing crucial peatland functions, such as peat accumulation and carbon (C) sequestration. In order to assess the success of restoration, we evaluated the seasonal carbon balances via carbon dioxide (CO2) and methane (CH4) emissions of different restoration techniques at two restored in-situ well pads, during two consecutive years. Restoration work involved: 1) the complete and partial removal of all introduced well pad construction materials, and spontaneous revegetation, or 2) the partial removal of foreign mineral soil, in addition to reintroduction of typical fen plant species such as Larix laricina, Salix lutea and Carex aquatilis. Comparisons were done with regional peatland reference ecosystems (REF) consisting of three peatlands: a wooded bog, a wooded poor fen and a wooded extreme-rich fen. While the average electric conductivity of restored sectors (946 µS cm-1) was higher compared to REF (360 µS cm-1), the pH was quite similar (pH 5.8 REF, pH 6 restored). Dissolved organic carbon concentration was lower in all restored sectors (5-11 mg l-1 restored sectors, 15-35 mg l-1 REF), presumably due to the still incomplete recovery of vegetation and lower organic matter content associated with remnant well pad material. Re-established plant communities had an important influence on the return of a C exchange in the different restoration outcomes, whereas introduction of plant species did not seem crucial. As a result, only when typical fen plant species had recolonized restored sectors, did we measure comparable seasonal C balance to REF. In areas where shallow open water had formed after the complete removal of all construction materials, then higher NEE was measured and these flooded sites remained net sources of C to the atmosphere. Considering C sequestration, we observe that the partial removal of the well pad mineral soil to near the water table level and the surface elevation of the surrounding ecosystem seems to be the most effective site management method. However, further research is needed to evaluate the suitability of this restoration method for the recovery of biodiversity.